Analisis Kemampuan Problem Solving Siswa Menggunakan Soal PISA Berbasis Islami Melalui Kegiatan Pengayaan - Mujib, Mujib (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2019)
This study aims to improve the ability of students' problem solving using Islamic-based PISA model questions through enrichment activities. The research subjects consisted of 5 fast group students who were given enrichment activities. The instrument was designed based on PISA questions with Islamic-based content quantity. Analysis of the improvement of students' problem solving abilities based on problem solving indicators compiled on each instrument problem based on Polya's problem solving steps namely Understanding the problem (M1), Arranging the plan (M2), Implementing the plan (M3), and Looking back (M4) . Based on the scores generated in field trials 1 (before enrichment) and field trials 2 (after enrichment) the scores of each indicator of problem solving have increased. Improvement occurs differently for each subject of research. The increase in scores indicates that there is an increase in the problem solving skills of each research subject. In general, in the field test stage 1, the subject did the problem solving stages of the M2 stage (preparing plans) and M3 (implementing plans) completion. The subject did not make the process of understanding the problem and did not look back. After the enrichment process was carried out on the five research subjects, the five subjects performed 4 stages complete poblem solving  with different scores. Keywords: Problem Solving, Problem Pisa Based on Islam, Enrichment